Yuletide in Dixie slavery, Christmas, and Southern memory - May, Robert E. 1943- (University of Virginia Press, 2019)
"Yuletide in Dixie scrutinizes two centuries of stereotypes about U.S. slaves' Christmases. Much has been written about Christmas in the antebellum South, but no book has tackled its place in master-slave relations, addressed black perspectives on holiday privileges, showed how these traditions disintegrated under the stress of the Civil War, or explained how antebellum Christmases were mythologized after the war--as they had been before it--in support of white supremacy. This volume brings to light this compelling story, with implications for contemporary disputes over displaying Confederate flags and preserving Confederate monuments"--
Includes bibliographical references and index
Keywords: Geschichte bis 1865; Slaves / Southern States / Social conditions; Slavery / Southern States / History; Christmas / Southern States / History; Collective memory / Southern States; Soziale Situation; Sklave; Brauch; Kollektives Gedächtnis; Weihnachten; Southern States / Social life and customs / 1775-1865; Southern States / Social life and customs / To 1775; USA -- Südstaaten